(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Ibn Taimiyah is one of the 13th century Islamic thinkers who made major contributions to various fields of science, including economics. This paper discusses in depth the main points of Ibn Taimiyah’s economic thoughts based on the principles of justice, the prohibition of usury and monopoly, state intervention in the market, and responsible ownership of property. The methodology used in this study is a literature review of Ibn Taimiyah’s works and modern literature that discusses his thoughts. The results of the study show that Ibn Taimiyah’s economic thoughts are very relevant to be applied in the contemporary Islamic economic system, especially in the context of wealth redistribution, business ethics, and solutions to social inequality. Human life cannot be separated from economic problems that affect human relations with other humans, these relationships must be based on Islamic religious norms that regulate all aspects of life including those related to mu’amalah problems. As part of our efforts to develop an Islamic economic system, we try to find a concept of the main ideas of his time as inspiration and guidance. For this reason, the author tries to convey the main ideas of one of the scholars, namely: Shaykhul Islam Ibn Taimiyyah, which relate to economic problems. He has very deep knowledge about Islamic teachings